Processamento sensorial e alimentação em crianças com desenvolvimento típico e com transtorno do espectro autista - Oliveira, Pâmela Lima de (2019)
This dissertation aimed to analyze the sensory systems and the presence of food selectivity, through the Protocol Sensory 1 - Questionnaire for Parents - 3 to 10 years (DUNN, 1999), clinical observation and Food Guide elaborated by the author of children with typical development e and a children with Autistic Spectrum Disorder (ASD), from three to ten years of age. The analysis included the correlation and comparison between the percentual results of Sensory Profile 1, with the presence of food selectivity, the number of foods consumed, the food groups, the food consistency, the attitude towards the new food and the variable prematurity. This was a quantitative cross-sectional study with a sample of 40 children, 20 children with typical development and 20 children diagnosed with ASD. For the analysis, the statistical software STATISTICA 9.1 was used, with the descriptive statistics tests, Mann- Whitney Non-Parametric Test, Student’s T-Test and Chi-square Association Test, considering a significance level of 5 %. As results of this research, a significant correlation was found between the percentage of alteration of the Sensory Profile in the group of children with ASD compared to the typical development group. The detailed observation of each item of the profile showed that the lower the value the greater the risk for the difference between the groups. We also found the presence of food selectivity, with less amount of food consumed, the restriction of the food group vegetables and meat and eggs and the non- acceptance of only a pasty food consistency in the group of children with ASD compared to the group in typical development. In addition, there was a significant result regarding the attitude towards food, in which the group with TEA presented a very negative attitude when compared to the typical developmental group. Finally, regarding the variable prematurity, no significant result was obtained, since they were premature children. The result of this dissertation allow e dust to conclude about the need for sensory evaluation, with a specialized occupational therapist, of food restriction cases, in addition to evaluations already performed with other health professionals such as pediatricians, nutritionists and speech- language therapists, since it was clear that the difficulties of the group of children with ASD originated in sensory issues since the risk of dysphagia and orofacial alterations were discarded in the analyzed group by their speech therapists.